Nonsurgical management of early-stage endometrial cancer due to obesity: a survey of the practice patterns of current Society of Gynecologic Oncology members - Aparna Kailasam; Giuseppe Cucinella; Angela J Fought; William Cliby; Andrea Mariani; Gretchen Glaser; Carrie Langstraat (Elsevier, 2023)
Objective: Nonsurgical management for endometrial cancer in patients with class 3 obesity (BMI ≥ 40 kg/m2) is a challenging scenario given lack of consensus on patient selection and treatment options. Our objective was to evaluate trends in practice patterns and physician opinions in the Society of Gynecologic Oncology (SGO) on nonsurgical management of endometrial cancer and complex atypical hyperplasia due to obesity. Methods: An online survey was sent to all gynecologic oncologist members of the SGO with questions centered on decision-making for nonsurgical approaches for patients with class 3 obesity patients. Fisher's exact tests were used to assess the associations between offering nonsurgical management and geographic region, practice type, and time in practice. Results: 255 (19.8 %) members from 6 geographic regions responded, of which 183 (71.8 %) offered primary nonsurgical management of endometrial cancer to patients with class 3 obesity and 72 (28.2 %) do not. The choice to offer initial nonsurgical management did not vary based on geographic region, time in practice or practice type. When asked to select BMI cutoff, the majority (65.2 %) started to offer nonsurgical management was BMI 60-64 kg/m2. Progesterone intrauterine device was the preferred treatment (68.3 %, 125/183). Of those who offered nonsurgical management, 97.3 % (178/183) recommended resampling in 3-6 months. Conclusion: Primary nonsurgical management of endometrial cancer in patients with class 3 obesity is offered by most gynecologic oncologists in SGO. However, almost one-third of gynecologic oncologists indicated they do not offer nonsurgical management for endometrial cancer for obesity alone. Additional data are needed to determine the safety of both approaches in these complex patients.